From Eutectic Clusters to Bulk Metallic Glasses of Zr–Al–Cu System1. Issue 10 (11th June 2013) - Chen, Jixiang; Zhou, Shuoyao
<x xml:space="preserve">Abstract</x> CuZr2 (MoSi2 type) phase structure is analyzed using clusters centered by two non‐equivalent atomic sites: small sphere Cu and large sphere Zr. It is shown that the clusters are all shared atoms in different ways with their neighboring clusters, so after sharing effective cluster should be put out to describe the alloy phase. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>